Whole Transcriptome Sequencing of Peripheral Blood Shows That Immunity/GnRH/PI3K-Akt Pathways Are Associated With Opioid Use Disorder - Dai, Qi; Pu, Shan-Shan; Yang, Xue; Li, Chang; He, Yafei; Liu, Xiaobo; Wang, Gang (Frontiers in Psychiatry, 2022)
Background: Opioid use disorder (OUD), which is most commonly exhibited as addiction, is a persistent chronic disease that places a great strain on families and society. A variety of peripheral traits have been linked to OUD in the past, but thorough research is insufficient. Methods: 7 male OUD patients and 7 male health controls with demographic and clinical data matched were enrolled in this study. Peripheral blood RNA was used to construct a rRNA removed library and a small RNA library. The peripheral transcriptome differences between the two groups were investigated using RNA-seq. Differentially expressed messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs) and microRNAs (miRNAs) were identified by bioinformatics methods and functional enrichment analysis with differentially expressed RNAs were performed to investigate the potential biological mechanisms for OUD. Results: A total of 229 mRNAs (115 up-regulated, 114 down-regulated), 416 lncRNAs (191 up-regulated, 225 down-regulated), 17 circRNAs (16 up-regulated, 1 down-regulated) and 74 miRNAs (42 up-regulated, 32 down-regulated) were differentially expressed between OUD group and health control group. Functional enrichment analysis with differentially expressed mRNAs showed that immunity, GnRH secretion, PI3K-Akt signaling pathways were associated with OUD. Immunity, JAK-STAT, and insulin-related pathways were enriched in functional enrichment analysis with targeted genes predicted by differentially expressed miRNAs. Conclusion: We identified hundreds of differentially expressed genes and they were enriched in immunity, GnRH secretion and PI3K-Akt signaling pathways. Some genes with significantly changed might be used as potential biomarkers for OUD progression and treatment.